Relasi antar Agama dalam Perspektif Fiqih - A. Bakir Ihsan (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2005)
There is a correlation between one's religious understanding and their attitude towards other religions. An exclusive understanding of religion has triggered the emergence of religious egocentrism, which considers other religions as wrong. This attitude is mainly fueled by a legalistic orientation that tends to be black and white and denies the truth of others. It is this biased legalistic orientation that needs to be reconstructed so that one-sided and exclusive understandings of religion can dissolve, ultimately breaking the rigidity of interactions between religious communities that have often been the seeds of unnecessary humanitarian tragedies. And this is the overarching theme that this journal seeks to address for the sake of peace on the earth we all inhabit together.